A method for dynamic balance training combining perturbed standing with sensory electrical stimulation - Worms, Georg (Rehabilitacija (Ljubljana), 2009)
Background: Dynamic balance training is an important treatment modality after stroke. We propose a novel method for balance training that utilises sensory electrical stimulation during perturbed stance in subjects with neurological impairment. The feasibility of this methodology is investigated in a case study with one chronic stroke patient. Methods: A dynamic standing frame was modified with electrical actuators which allow the application of unexpected perturbations to neurologically impaired people during standing, while protecting the subject from falling. The subject underwent two different periods of perturbation training, each lasting ten days. During the first period the subject was perturbed in eight different directions. During the second period the subject was also perturbed, but was assisted by sensory electrical stimulation of the soleus (SOL), tibialis anterior (TA), tensor fascia latae (TFL), and vastus muscles (VAS) in the impaired leg. After each period of training, an assessment was carried out to measure the forces the subject applied on the ground via two force plates and the EMG responses of the SOL, TA, TFL, and VAS muscles. Results: The subject improved his ability to balance throughout the training, with the largest improvements occurring during the final period when sensory electrical stimulation was used. Conclusion: These observations verify the feasibility of the approach and suggest that sensory electrical stimulation may have beneficial effects on balance training.
Keywords: električna stimulacija; ravnotežje; dinamično urjenje